ANALISIS DEIKSIS DALAM NOVEL BERJALAN DALAM KABUT KARYA KAREN KINGSBURY - Ndruru, Megasari (Universitas Nias Raya, 2024)
Deixis is one of the objects of pragmatic studies which examines demonstrative words in conversation and of course in a literary work, especially novels, there are also several deixis, including person, demonstrative, place, time and discourse deixis. This research aims to describe deixis in the novel Walking in the Mist by Karen Kingsbury. The type of research is qualitative research with a content/document analysis approach. The data collected by researchers came from the novel